Irrigation modulates the effect of increasing temperatures under climate change on cotton production of drip irrigation under plastic film mulching in southern Xinjiang - Wang, Hongbo; Yin, Zi; Zhang, Lei; Zhao, Fengnian; Huang, Weixiong; Wang, Xingpeng; Gao, Yang (Frontiers in Plant Science, 2022)
Introduction Warming and drought brought about by climate change seriously harm sustainable agricultural production in southern Xinjiang. It is still unclear how irrigation can improve the ability of crops to cope with climate change. Methods Therefore, in this study, we calibrated and validated the AquaCrop model using data collected in cotton production from 2017 to 2018. The model effectively simulated the growth, biomass, and yield of cotton plants at the experimental site under different warming and irrigation conditions. The meteorological data collected from 1987 to 2016 were used in a simulation to predict cotton production under 3 temperature scenarios (temperature increased by 0°C, 1°C, and 2°C) and 6 levels of irrigation (198, 264, 330, 396, 495, and 594 mm) to explain the modulating effect of plastic film mulching-coupled drip irrigation on cotton production in terms of increasing temperatures under climate change in southern Xinjiang. Results and discussion Model prediction showed that an increase in temperature reduced cotton yield under a low irrigation level, while an increase in irrigation mitigated the impact of climate change on cotton yield. An increase of 1°C did not significantly reduce cotton yield at 198–330 mm of irrigation. Under a 2°C increase, 396–594 mm of irrigation was required to ensure plant growth and yield formation. Both aboveground biomass and yield increased with the rise in the irrigation level at the same temperature. High water use efficiency was achieved at 495 mm of irrigation without significant yield loss. Therefore, in the low-temperature scenario, it can be preferentially considered to achieve sustainable water use through water management, while in the high-temperature scenario innovative agricultural measures are required to avoid yield loss. Optimizing irrigation strategies can reduce warming-induced damage to crops under climate change.